Content validity of the Japanese version of the health literacy and resiliency scale for youth with chronic illness - Sekine, Saya; Kobayashi, Kyoko; Ochiai, Ryota; Higaki, Takashi (Frontiers in Pediatrics, 2022)
Health literacy, the ability to find, understand, and use information and services to make informed health-related decisions and actions, is essential for youths with chronic diseases to adapt to and live with their illnesses. However, no appropriate measurement of a child's health literacy has been developed in Japan. The Health Literacy and Resiliency Scale for Youth (HLRS-Y) was developed by Kathy Bradley-Klug and her colleagues to assess health literacy, resiliency, and self-advocacy/support of youth aged 13-21 years with chronic illness in the U.S. This study aimed to develop the Japanese version of the HLRS-Y and test its content validity. After receiving the original authors’ approval, four nursing researchers with expertise in paediatric nursing translated the scale into Japanese (forward translation). Afterward, the appropriateness of each expression was examined by a paediatrician. Then, an English native speaker back-translated this into English (back-translation). We reported the back-translated version to the original author to confirm the accuracy. The scale's content validity index (CVI) was evaluated by professionals working in paediatric, transitional care, and adult health care areas. Eleven participants responded to an online survey to check for content validity. Of the 36 items, 34 met the I-CVI criteria. There were two items which did not exceed the criterion value but approximated it. The values of S-CVI/Ave were 0.96, which met the criteria. From the results, it was confirmed that the Japanese version of the HLRS-Y had good content validity. Future studies should examine factor validity, known group validity, and reliability of this scale.